Fiscal Policies for Achieving Finland's Emission Neutrality Target - Parry, Ian (IMF Working Papers; Working Paper, 2021)
Finland has pledged to cut net greenhouse gas emissions to zero by 2035 and has sectoral targets for deploying electric vehicles, phasing out coal generation, and oil-based space heating. Fiscal policies at the national and sectoral level could play a critical role in achieving these objectives. Carbon dioxide emissions are already priced significantly in Finland but prices vary substantially across fuels and sectors. The paper discusses a reform to both scale up, and progressively harmonize, pricing while using revenues to address equity issues. It also discusses the potential use of revenue-neutral feebate schemes to strengthen mitigation incentives for the transportation, industry, building, forestry, and agricultural sectors.